Effectiveness of a Rehabilitation Self-Efficacy Program on Postoperative Outcomes in Older Adults with Hip Fracture: A Randomized Controlled Trial - Rittharomya, Jintana; Krua-aum, Pornnapa; Aree-Ue, Suparb (Pacific Rim International Journal of Nursing Research, 2024)
Older adults with hip fractures who have undergone surgery require long-term care to relieve pain, improve physical function, and enhance their quality of life. Thus, continuing care postoperatively is imperative for quick recovery. This randomized controlled trial examined the effectiveness of a rehabilitation self-efficacy program to enhance postoperative outcomes, including self-efficacy exercise, pain, activities of daily living, strength of muscles, and quality of life. Fifty-eight Thai older adults were randomly assigned to the intervention (n = 29) or control groups (n = 29). The intervention group received the eight-week intervention, while the control group received only usual care. Data were collected through questionnaires including the Self-efficacy Quadriceps and Gluteal Exercise Questionnaire, Numeric Pain Rating Scale, Modified Barthel Activity of Daily Living Index, and Mini-osteoarthritis of Knee and Hip Quality of Life Questionnaire. A hand-held Dynamometry was used to assess quadriceps muscle strength. Data were analyzed by descriptive statistics and a two-way multivariate analysis of variance with repeated measures. The results revealed that the intervention group showed significantly higher self-efficacy in exercise and activities of daily living as well as reduction of pain, than the control group at discharge, and 2 and 8 weeks after hospital discharge. The quadriceps muscle strength and quality of life of the intervention group were significantly higher than that of the control group at 8 weeks after hospital discharge. It can be concluded that this program is effective. Nurses should integrate into this program in practice to enhance overall care quality for older adults with hip fractures. However, further testing in various settings is required before the program is widely used.